Experimental non-equilibrium radiation measurements for low-Earth orbit return - Glenn, AB; Collen, PL; McGilvray, M (American Institute of Aeronautics and Astronautics, 2021)
This paper reports on absolute radiation measurements performed in synthetic air (20.78% O2, 79.22% N2) shock-heated flows. Experiments were carried out in the Oxford T6 Stalker Tunnel in Aluminium Shock Tube mode. Data is presented for velocities ranging from 5.5-7.2 km/s at a nominal 1 bar post-shock pressure, in both UV/Vis and Vis/NIR spectral ranges. Simulations of the equilibrium radiance using NASA CEA and NEQAIR codes underpredict that obtained from the experimental data. An analysis using the newly developed LASTA code removes shock deceleration from consideration as a cause for this discrepancy. Non-equilibrium data is analysed in the form of spectral and absolute non-equilibrium metrics, and the effects of shock speed and post-shock pressure on the non-equilibrium radiance isolated. Finite-rate one-dimensional two-temperature simulations using POSHAX3 with Park 1993 rates are performed, which significantly underpredict the experimentally acquired data.